Cost evaluation of current uprating of overhead transmission lines using ACSR and HTLS conductors - Nuchprayoon S. (2017)
© 2017 IEEE. This work presents cost evaluation of current uprating of overhead transmission lines by using Aluminum Conductor Steel Reinforced (ACSR) and High Temperature Low Sag (HTLS) conductors. The evaluation method is carried out based on twofold and fourfold ampacities, under both normal and stressed operating conditions. The test case is a 230-kV, double-circuit, transmission lines using 1272 MCM ACSR conductors. The candidate conductors are five types of HTLS conductors with comparable size. The cost components under consideration are demolition cost, construction and installation costs, conductor cost, cost of energy losses, and land cost. Upon evaluation of the total costs, the selection criteria of proper conductor are proposed.